Determining protein denaturation of sardine (Sardina pilchardus) marinates before and after the maturation. Issue 9 (20th June 2019) - Dericioglu, Buse Nihan; Alak, Gonca; Atamanalp, Muhammed
Abstract: In this study, sardine fish ( Sardina pilchardus ) was subjected to marination at different degrees of acidity (2.5%–5%). On the basis of the duration of maturation (22 days) and postmaturation period (three months after maturation), protein denaturation and quality changes of marinades were determined. Quality parameters, such as pH, acidity, salinity, and lipid oxidation, were examined for both periods. As a result of the study carried out for 22 days at different acidity levels, the change in the amount of TVB‐N was found to be insignificant ( p > 0.05), but the differences in pH, TBARS, acidity, and salinity levels were found to be significant ( p < 0.05). In the postmaturation period, the change in the TBARS amount was insignificant ( p > 0.05), and the other parameters were found to be significant ( p < 0.05). SDS‐PAGE analysis showed that fish muscle and brine proteins showed different profiles and a decrease in densities of MHC, actin, and TM bands during the maturation period was observed. Practical applications: Protein denaturation is important in fisheries products, so multiple verification tests should be performed to monitor this process. It was suggested that DSC and SDS‐PAGE techniques are easier and quicker analyses for determining protein denaturation in seafood products compared with traditional techniques.